Wykorzystanie metody projektów na zajęciach przyrody w klasie III szkoły podstawowej - Karolina Żyra (Problemy Wczesnej Edukacji)
This article describes experiences gained during work with the project approach on science lessons in Grade 3 of Primary School. They are analyzed in the light of action research and the theoretical base of constructivism. The conclusions from the analysis confirm the usefulness of the project approach in stimulating the children’s potential and their independence during science lessons.